Islam dan Masyarakat Ideal (Ummatan Wasathan) dalam Perspektif Para Mufassir dan Relevansinya dengan Kontak Keindonesiaan Masa Kini dan Depan - Aziz, Nasaiy (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
Islam as the source and path of truth that comes from Allah is a view of life which is not only intended for the welfare and happiness of Muslims, but is a blessing for all nature. Islam which is derived from divine truth, both contained in the verses of the Koran and the sunnah of the Prophet, is a guide for the way of all times. Likewise, Islam regulates the relationship between humans and others, with God and with their natural environment. The key to the personality of the Islamic community is akidah, syari'at and morals. If the creed provides the direction of the movement of society, while the syari'at provides limits on how and the method to take that direction properly, then morals will decorate the path of the goal so that it is beautiful and pleasant. The ideal society or in this study is referred to as the